Driving Customer Decisions Through Interest: The Role of Brand Image and Promotion in BRI Simpedes Si Serba Bisa - Yogaswara, Indra; Widayat, Widayat; Juanda, Ahmad (Business Innovation Management and Entrepreneurship Journal (BIMANTARA), 2025)
This study aims to analyze the influence of brand image and promotion on the decision to open a Simpedes Si Serba Bisa account, focusing on interest in opening an account. Quantitative explanatory research uses a quantitative approach and data collection methods by distributing questionnaires. The sample in this study amounted to 160 respondents. The SEM-PLS method was used in data analysis and testing with the help of the SmartPLS-4 application program. The study results indicate that a positive brand image, which includes reputation, service quality, trust, visual impression, and previous customer experience, significantly increases the interest of prospective customers in opening an account. In addition, the intensity and effectiveness of promotion also play an important role in shaping this interest. Targeted promotions through advertisements in print media, television, radio, and digital platforms, as well as incentives such as direct prizes and special discounts, have been shown to increase public awareness and interest in the Simpedes Si Serba Bisa service to open an account. High interest in this product ultimately drives customers' decisions to open an account. This study confirms that effective promotional strategies and a strong brand image are key to influencing customer decisions, with practical effectiveness for banks to optimize customer growth and expand market share in Padalarang.